Quantitative models for operational risk: Extremes, dependence and aggregation - Chavez-Demoulin, V.; Embrechts, P.; Nešlehová, J. (Journal of Banking & Finance, 2006)
Due to the new regulatory guidelines known as Basel II for banking and Solvency 2 for insurance, the financial industry is looking for qualitative approaches to and quantitative models for operational risk. Whereas a full quantitative approach may never be achieved, in this paper we present some techniques from probability and statistics which no doubt will prove useful in any quantitative modelling environment. The techniques discussed are advanced peaks over threshold modelling, the construction of dependent loss processes and the establishment of bounds for risk measures under partial information, and can be applied to other areas of quantitative risk management.1This paper was presented as an invited contribution at the meeting “Implementing an AMA for Operational Risk”, Federal Reserve Bank of Boston, May 18–20, 2005.1